Sound propagation in 3D spaces using computer graphics techniques - Charalampous, Panagiotis; Michael-Grigoriou, Despina (My University, 2014)
Sound propagation in 3D spaces is governed by similar physical principles as light. As a result, sound rendering in a 3D virtual environment can benefit from methods developed for graphics rendering and vice versa. In this review, we provide an overview of methods used for sound rendering that share concepts and techniques with graphics rendering. Firstly we describe geometrical propagation techniques where the computations are based on ray theory similar to ray tracing techniques in computer graphics. Secondly, we review numerical techniques. These techniques, similar to the idea of radiosity, are based on the subdivision of the space into elements. Then we describe acceleration techniques that can be used in combination with other methods to speed up calculations. Lastly, for the sake of completeness, a quick overview is given of sound computation techniques that simulate specific sound effects that do not apply on illumination. The aim of this survey is to share knowledge among the two disciplines using familiar and known concepts.
Keywords: Acoustic wave propagation; Computation theory; 3-D virtual environment; Computation techniques; Sound propagation